Motivasi, Kualitas Sumber Daya Manusia Mempengaruhi Kinerja Karyawan Pada Toko oleh-oleh Keranjang Bali - Nurnaningsih, Nurnaningsih (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
The research investigates the impact of human resource quality and work motivation on employee performance at The Keranjang Bali, using a quantitative approach to analyze intrinsic and extrinsic motivational factors. Results indicate that both human resource quality and work motivation significantly and positively influence employee performance, with statistical tests showing strong correlations between these variables. The study employs various motivational theories, including Maslow’s needs theory, and considers contextual factors like organizational culture in assessing employee performance levels. Employee motivation is linked to increased productivity and enthusiasm, which can lead to higher sales and better customer service in retail businesses like The Keranjang Bali. The research highlights the importance of managing human resources effectively to enhance employee performance, suggesting programs like career advancement opportunities and job security to improve motivation.The results of the multiple linear regression analysis yield the equation: Y = 2.781 + 0.568 X₁ + 0.330 X₂ + e, indicating that Human Resource Quality (X₁) and Work Motivation (X₂) significantly influence Employee Performance (Y). Based on the t-test hypothesis, the calculated t-value for X₁ is 5.119, which exceeds the critical t-value of 2.004. Similarly, the calculated t-value for X₂ is 4.133, also greater than the critical t-value of 2.004. Therefore, it can be concluded that both independent variables, X₁ and X₂, have a significant and positive impact on the dependent variable (Y). Furthermore, the F-test indicates a significance value of 0.000, which is less than 0.05, and an F- calculated value of 47.741 that surpasses the F-table value of 3.61. This suggests that the variables X₁ and X₂ collectively have an effect on variable Y. The coefficient of determination shows a value of 0.635 or 63.5%, meaning that Human Resource Quality and Work Motivation together account for a 63.5% influence on Employee Performance, while the remaining 36.5% is affected by other variables not covered in this study.